Identification of Effective Factors on Academic Performance of Talented Students in Iranian Universities: A Meta-Synthesis Study - Parinaz Rahmani Barouji; Jamal Haji; Mojgan Mohammadimehr (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: Talented students, being perceived as individuals capable of performing tasks better than others and making significant contributions toward solving environmental, societal, and national challenges, are considered valuable human resources in any society. The present study aimed to identify the factors influencing the academic performance of talented students. Methods: The methodological approach of this study was qualitative, and the adopted research method was the seven-step meta-synthesis approach by Sandelowski and Barroso.The researchers conducted a systematic search of studies related to these factors in academic databases, such as the Scientific Information Database (SID), Noormags, Magiran, the Comprehensive Humanities Portal, Civilica, and Elmnet. The search spanned the years 2006-2024 using keywords, such as "talented students," "academic performance of gifted students," and "factors influencing the academic performance of talented students." In the initial review, 136 references were identified. After screening and validation steps and using the Critical Appraisal Skills Programme (CASP) tool, a total of 32 studies were analyzed through thematic analysis. To assess the quality or reliability of the indicators, the Kappa coefficient in IBM SPSS Statistics Software Version 26 was utilized, which in this study was calculated as 0.813, indicating a satisfactory reliability level for the indicators used. Results: From the content analysis of the selected sources, 240 initial codes were extracted, encompassing 16 sub-themes. These sub-themes were organized into four main themes: individual factors (demographic characteristics, cognitive and psychological components, motivational traits, attitudinal traits, behavioral traits, family characteristics and conditions); organizational factors (organizational culture and climate, intra- and inter-university interactions, characteristics of the university of study); supportive factors (support and backing from the community, support and backing from the government, support and backing from the university); educational factors (development of student talent and abilities, educational strategies, development of educational content, educational facilities and resources) Conclusion: The factors affecting the academic performance of talented students are multidimensional. In addition to the individual characteristics of the student, they are also influenced by factors at the university and social environment. Therefore It is recommended that educational administrators and planners, considering the individual, organizational, supportive, and educational factors affecting the performance of talented students, which were explained in this study, provide a suitable platform for the advancement and improvement of these students' academic performance in universities.